Specific Localization of the Drosophila Telomere Transposon Proteins and RNAs, Give Insight in Their Behavior, Control and Telomere Biology in This Organism. - Elisenda López-Panadès; Elizabeth R Gavis; Elena Casacuberta (PLoS ONE, 2015)
Drosophila telomeres constitute a remarkable exception to the telomerase mechanism. Although maintaining the same cytological and functional properties as telomerase maintain telomeres, Drosophila telomeres embed the telomere retrotransposons whose specific and highly regulated terminal transposition maintains the appropriate telomere length in this organism. Nevertheless, our current understanding of how the mechanism of the retrotransposon telomere works and which features are shared with the telomerase system is very limited. We report for the first time a detailed study of the localization of the main components that constitute the telomeres in Drosophila, HeT-A and TART RNAs and proteins. Our results in wild type and mutant strains reveal localizations of HeT-A Gag and TART Pol that give insight in the behavior of the telomere retrotransposons and their control. We find that TART Pol and HeT-A Gag only co-localize at the telomeres during the interphase of cells undergoing mitotic cycles. In addition, unexpected protein and RNA localizations with a well-defined pattern in cells such as the ovarian border cells and nurse cells, suggest possible strategies for the telomere transposons to reach the oocyte, and/or additional functions that might be important for the correct development of the organism. Finally, we have been able to visualize the telomere RNAs at different ovarian stages of development in wild type and mutant lines, demonstrating their presence in spite of being tightly regulated by the piRNA mechanism.